Anthropometry and body composition of 18 year old men according to duration of breast feeding: birth cohort study from Brazil. Issue 7420 (16th October 2003) - Victora, Cesar G; Barros, Fernando; Lima, Rosângela C; Horta, Bernardo L; Wells, Jonathan
Abstract: Objective To assess the association between duration of breast feeding and measures of adiposity in adolescence. Design Population based birth cohort study. Setting Pelotas, a city of 320 000 inhabitants in a relatively developed area in southern Brazil. Participants All newborn infants in the city's hospitals were enrolled in 1982; 78.8% (2250) of all male participants were located at age 18 years when enrolling in the national army. Main outcome measures Weight, height, sitting height, subscapular and triceps skinfolds, and body composition (body fat, lean mass). Results Neither the duration of total breast feeding nor that of predominant breast feeding (breast milk plus non-nutritive fluids) showed consistent associations with anthropometric or body composition indices. After adjustment for confounding factors, the only significant associations were a greater than 50% reduction in obesity among participants breast fed for three to five months compared with all other breastfeeding categories (P = 0.007) and a linear decreasing trend in obesity with increasing duration of predominant breast feeding (P = 0.03). Similar significant effects were not observed for other measures of adiposity. Borderline direct associations also occurred between total duration of breast feeding and adult height (P = 0.06). Conclusions The significant reduction in obesity among children breast fed for three to five months is difficult to interpret, as no a priori hypothesis existed regarding a protective effect of intermediate duration of breast feeding. The findings indicate that, in this population, breast feeding has no marked protective effect against adolescent adiposity.